Counter-Terrorist Security: the Example of the Special Powers of the Polish Special Services in the Field of Surveillance of Foreign Nationals - Rosicki, Remigiusz (My University, 2018)
The material scope of the analysis presented in this paper refers to special powers held by the Polish special services with respect to the surveillance of foreign nationals in connection with terrorist threats and terrorist offenses. This paper connects the issue of anti-terrorist measures with the assessment of the effectiveness of the Polish special services and with the assessment of potential social costs, which are related to the increase in the powers held by these services in the field of surveillance of Polish citizens and foreign nationals. The analysis of the powers of the special services focuses on the powers of one of the counterintelligence services, i.e. the Internal Security Agency (Polish: ABW). The purpose of this paper is to indicate the consequences of the introduction of legal changes concerning the powers held by the special services in the scope of applying particular types of surveillance activities (operational-and-intelligence activities). It poses the following research questions: (1) To what extent can mechanisms in Polish law influence the effectiveness of combating terrorism by the Polish special services? (2) To what extent can mechanisms in Polish law in the field of combating terrorism violate the rights and freedoms of Polish citizens and foreign nationals? In order to answer the research questions, the activities and powers of Polish special services were analyzed from a legal and institutional point of view. On the other hand, to analyze legal regulations related to surveillance, the author applied a dogmatic and doctrinal interpretation and a pro-constitutional interpretation of the provisions of criminal law.
Keywords: Bezpieczeństwo; Security; Bezpieczeństwo antyterrorystyczne; Anti-terrorist safety; Bezpieczeństwo informacji; Information security; Przestępstwa terrorystyczne; Terrorist offenses; Terroryzm; Terrorism; Inwigilacja; Surveillance; Służby specjalne; Special services